Analisis Peningkatan Kemampuan Kognitif Murid Pada Fase F Elemen Pemrograman Web Setelah Menggunakan Lms Weboost - Rendi Eko Kurniawan; Ersha Aisya Elfaiz (CV. SINAR HOWUHOWU, 2026)
Students' cognitive abilities in the Web Programming element at the vocational secondary school level remain a persistent challenge in the implementation of Phase F of the Merdeka Curriculum, particularly in the mastery of programming concepts and problem-solving within lines of program code. This study aims to analyze the improvement of cognitive abilities among Class XI RPL students at SMKS YPM 4 Taman in the Web Programming element following the use of a website-based Learning Management System (LMS) entitled WeBoost, integrated with the Problem Based Learning (PBL) instructional model. The study employed a one-group pretest-posttest design conducted from April 20 to 29, 2026. Cognitive ability data were collected through pre-test and post-test instruments that had been validated by subject matter experts, yielding a validity percentage of 98.75%, categorized as Very Valid. Inferential analysis using the Paired Sample T-Test revealed a calculated t-value of 34.88 with 40 degrees of freedom (df) and a p-value of less than 0.001, indicating a statistically significant difference in students' cognitive abilities between the pre-intervention and post-intervention conditions. The magnitude of cognitive improvement was further assessed using the Normalized Gain (N-Gain) test, which produced a mean score of 0.721, classified within the high gain category. These findings indicate that LMS WeBoost is both significantly and effectively capable of enhancing students' cognitive abilities in the Web Programming element of Phase F.